Chronology and documentary handbook of the State of Alaska. - Trover, Ellen Lloyd (Chronologies and documentary handbooks of the States ;, 1972)
Contains a chronology of historical events in Alaska, a biographical directory, an outline of the state constitution and selected documents pertinent to Alaskan history.